Association Between Birth Weight and Quality of Life in Early and Middle Adolescence - Eva Latifatun Ni'mah; Dimas Tri Anantyo; Adhie Nur Radityo Suswihardhyono; Teddy Wahyu Nugroho (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Children with low birth weight tend to have a higher risk of experiencing abnormal growth and developmental delays. While the risk of developing obesity in the later years is higher in children with high birth weight. Physical and psychological conditions can affect the quality of life of adolescents.Objective: To analyze the association between birth weight and quality of life in early and middle adolescents.Methods: This cross-sectional study involved 120 students aged 13-16 years in Semarang City in which a consecutive sampling method was used.  The study was conducted in August 2020. Research subjects need to fill up the PedsQL, PAQ, birth history, and socio-economic questionnaires. Statistical analyses used were Chi-square and logistic regression tests.Results: Birth weight was significantly associated with quality of life (p=0.002). A history of abnormal birth weight increases the risk of experiencing poor quality of life as a teenager (p=0.002; OR=3.987). Low birth weight was associated with decreased physical function (p=0.001), whereas high birth weight was associated with reduced social and school functioning (p=0.013; 0.032). Gender was significantly associated with quality of life (p=0.016). Girls tend to have a higher risk of experiencing poor quality of life (p=0.021; OR=4.021).Conclusion: Birth weight has a significant association with quality of life in early and middle adolescents. Adolescents with a history of LBW or HBW were more likely to experience decreased quality of life than adolescents with a history of NBW.Keywords: Adolescence, Birth weight, Quality of Life.